PKM AKSESORIS MANIK HANDMADE DI WILAYAH SURABAYA - Sharasanti, Diah Anugerah; Devica, Sadana; Tedjokusumo, Edith Primadiana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
The community partnership service (PKM) intended to solve two partnerships’ economy social problems of UKM Tine’s Collection and KSM Kakap Merah 2 which engage in producing handmade accesories. Both partners are located on Tambak Sari subdistrict and Kenjeran subdistrict in Surabaya. The problems are (1) in management, there is lack of understanding of both partners in managing business and there is no entrepreneurial spirit; (2) in production, the products are still very simple, and ordinary; (3) in marketing, the product selling is also very simple; (4) in accounting, the parteners never record and manage the finance professionally. The results of this community partnership service are the enhancement of partners’ motivation in entrepreneurship, the improvement of products’ quality, the increasement of turn over, marketing by social media, and the awareness in bookkeeping. The suggestion for this service is the consistency of having training and support for a year for the partners to implement the knowledge and skills that both partners received to manage the business more professional, the product designs are developed as market demand and fashion trend.